Diversification of crops and food security: the role of family farming in the COVID-19 pandemic - Milena Almeida Vaz; Hermeson dos Santos Vitorino; Alessandro Medeiro Evaristo; Daniela Rosa Alves da Silva Pereira; Edson Lourenço da Silva; Fernanda Luz Costa; Tamaris Gimenez Pinheiro; Denise Dias da Cruz (Revista Brasileira de Ciências Ambientais)
Given the importance of family production, our aim was to characterize the productivity and importance of family production during the COVID-19 pandemic in the communities of Engano dos Rodrigues and Lagoa Seca, located in the municipality of Santana do Piauí. Data were collected by monitoring production and sales, from interviews and analysis of the strengths, weaknesses, opportunities, and threats (SWOT) matrix. The strengths of the activity lie in the diversity of food products and the continuous production of most items, in the organization into an association and the partnerships established, which were crucial at a time of crisis to guarantee the distribution and sale of agricultural products. The weak points are mainly related to the lack of technical assistance. Understanding the dynamics of agroecological family production in times of crisis highlights the importance of institutional support and continuing education for the resilience and sustainable development of rural communities. We also stress the importance of future research focusing on the impact of public policies on family farming in the semiarid region, as well as the effectiveness of different marketing and cooperation strategies among farmers.